Letter (copy) : S.S. "Yorkbrook" - Citrine, Walter, 1887-1983
011-0107-001 WMC/WJB/AC/589 International 24th March, 1937. Mr. W. Schevenels, International Federation of Trade Unions, 9, avenue d'Orsay, PARIS VIIe. Dear Comrade Schevenels, S.S. "YORKBROOK". With further reference to your letter of 18th March, the result of our enquiries shows that this vessel was at the port of Great Yarmouth on September 12, 1936, with a cargo of deals, battens, and boards and box wood, her nett tonnage being 718 tons. After discharging that cargo, she was put in ballast, and proceeded to Helsingfors. These particulars have been given by the Port Haven Commissioners and the Custom House. The vessel is owned by a man named Jacobsen, and is managed by the firm mentioned in your letter, namely, Charles Strubin & Co. Ltd., London. Further, we are informed that she sailed under the British flag until August, 1935, when she was transferred to the Estonian flag, under which she still sails. We are pursuing our enquiries, and if we receive any more information we will write to you again. Yours faithfully, General Secretary. 292/946/11/107